From phosphorescence to delayed fluorescence in one step: tuning photophysical properties by quaternisation of an sp2-hybridised nitrogen atom. Issue 25 (9th June 2022) - Klimash, Anastasia; Prlj, Antonio; Yufit, Dmitry S.; Mallick, Abhijit; Curchod, Basile F. E.; McGonigal, Paul R.; Skabara, Peter J.; Etherington, Marc K.
Abstract : Switching on thermally activated delayed fluorescence through quaternisation of an sp 2 -hybridised nitrogen atom. Abstract : Control of the delayed emission of organic compounds is an important factor in the development of new display technology and for the emerging use of organic emitters in sensing and fluorescence microscopy. In particular, there is a need to understand how the phenomena of room-temperature phosphorescence and thermally activated delayed fluorescence intersect. Here, we show that delayed fluorescence can be activated in room temperature phosphorescence emitters by quaternising the sp 2 -hybridised heterocyclic nitrogens. Furthermore by judicious positioning of a carbazole donor in the meta - or para -position with respect to the ring nitrogen atom, structural and sterical influences combine to tune the origins of the delayed fluorescence from triplet–triplet annihilation to thermally activated delayed fluorescence. Crucially, the quaternisation of nitrogen provides us with the means to fine-tune singlet and triplet states in a predictable manner, uncover the intersection between phosphorescence and delayed fluorescence and tip the balance in favour of delayed fluorescence.